Natural Resource Exports, Fiscal Policy Volatility and Growth. (7th July 2014) - Bleaney, Michael; Halland, Håvard
Abstract The combination of poor institutions and erratic macroeconomic policy, as measured by the volatility of fiscal policy, is associated with slower growth. We show that macroeconomic policy is more erratic in countries that are rich in natural resources, especially minerals and fuels, and in those that receive large aid inflows. Poor institutions also play a role. Although Africa is a major receiver of aid and exporter of natural resources, this is not purely an African phenomenon. Output volatility is not associated with slower growth after controlling for institutions and the volatility of fiscal policy.